Corollary discharge signals in the cerebellum - Person, Abigail L (Biol Psychiatry Cogn Neurosci Neuroimaging, 2019)
The cerebellum is known to make movements fast, smooth and accurate. Many hypotheses emphasize the role of the cerebellum in computing learned predictions important for sensorimotor calibration and feedforward control of movements. Hypotheses of the computations performed by the cerebellum in service of motor control borrow heavily from control systems theory, with models that frequently invoke copies of motor commands, called corollary discharge (CD). This short review describes evidence for CD inputs to the cerebellum and highlights the hypothesized roles for this information in cerebellar motor-related computations. Along with the companion review, we hope to compare insights into the role of CD in motor control, described here, to its exciting but still untested roles in cognition, perception and thought control described in Moberget and Ivry.